Assessment of Warming in the Different Elevation of the Water Basin Area in Nepal - Bista, Raghu Bir; Khadka, Bimal; Khatri , Bishnu Bahadur (Journal of Ecohumanism, 2025)
This study examines warming in the different elevations in the water Basin in Nepal. Using time series data sets of temperature variables from 1980 to 2020 collected from the Department of Hydrology and Metrology (DHM), Nepal, this study employs descriptive statistics, a time series-forecasting model, and Mann Kendal test and Sen’s test to trace out temperature variable movement and potential results. As a result, we find rising temperature is +1.10c y-1 with +0.0270c y-1 and rising Tmin, and T max by +2.10c y-1 and +3.30c y-1 in all elevations from 205 m to 2744 m and decadal period in the last 40 years from 1980 to 2020. Except for the second time zone (1990-1999), Sen’s Coefficients and Kendel’s Tau of these remaining three time zones have a positive trend. It implies raising Tmean with more than +20c y-1 temperature difference between Tmin, and T max. It results in warming the water basin. We conclude that the basin’s small cities and three ecological belts at present and in the future will be in threat of climate catastrophe. In mountain, the frequency of ice melting in Annapurna Mountain will be higher than the estimated value. The risk of flood in the summer season will be disastrous in the hills and the plain cities. Wildlife and crop cycle will be in the heat risk. Households may fall in extreme vulnerability and potential migrants. The result will be valuable inputs to scale up effective monitoring and tracking systems on climatic variables and climate change for further analysis and prediction. Further, the study will be helpful empirical insights to initiate resilient measures as appropriate to different elevations and households’ resilient capacity, along with zero-cost indigenous knowledge and technology.